A “Necessary Evil”: Staff Perspectives of Soft Restraint Kit Use in a High-Security Hospital - Walker, Helen; Tulloch, Lindsay (Frontiers in Psychiatry, 2020)
Introduction: Forensic mental health nurses working at the forefront of services can intermittently face enduring and somewhat harrowing or stressful situations. Enclosed is an example of the use of mechanical restraints (Soft Restraint Kit) for a two month period. Staff experience of working under such circumstances is an under reported area. Method: The experience of nursing a patient under extreme conditions was captured through use of a qualitative study, using semi structured interviews with a purposive sample of (n=10) staff nurses and nursing assistants in a high secure hospital. Results: Thematic analysis was undertaken generating four themes: sense of responsibility, aptitude, enablers / inhibitors and consequence. Conclusions suggest that Soft Restraint Kits provide a useful method of containment, although prolonged use presents considerable challenges for staff. The importance of preparation and training cannot be underestimated and continued support and supervision are absolutely essential.